Subthalamic nucleotomy alleviates parkinsonism in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-exposed primate. - Aziz, T; Peggs, D; Agarwal, E; Sambrook, M; Crossman, A (1992)
Research into the neural mechanisms underlying the symptoms of parkinsonism utilizing the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-exposed primate model have shown that the subthalamic nucleus (STN) occupies a central role. As a logical development of this theory, we have studied the effects of thermocoagulative lesions of the STN in the primate model. Such lesions can cause remarkable symptom reversal in the experimental primate model.